Diaper dermatitis among children in Ibadan, Nigeria: frequency and predisposing factors. - Owa, A.B.; Oladokun, R.E.; Osinusi, K. (European Journal of Pediatric Dermatology, 2016)
Diaper dermatitis (DD) is one of the commonest skin conditions in infants and young children. It accounts for frequent hospital visits and is a cause of discomfort to children and parental anxiety. There is paucity of information on DD and predisposing factors among African children. The objectives of this study were to determine the prevalence of DD among children in Ibadan, Nigeria and to identify factors associated with the condition. In this cross-sectional study, 424 children aged 2 days to 23 months were randomly selected from eight immunisation clinics within Ibadan metropolis. Information collected included socio-demographic data, diaper practices and nutritional history. The diaper area was inspected for the presence of dermatitis. The characteristics and extent of the lesions were noted. Dermatitis was graded as mild, moderate or severe. The prevalence of DD was 38.9%. Using multivariate analysis, factors associated with a current episode of DD included age less than six months, previous history of DD, low social class, recent antibiotic use, use of non-breathable disposable diaper and recent history of diarrhea. Diaper dermatitis is a common problem among Nigerian children. Some of the factors predisposing to this condition can be modified in order to reduce its prevalence.